The Mediating Effect of Business Performance on the Relationship between Financial Literacy and MSMEs’ Loan Repayment Performance - Oktaviani, Luh Gede Adilia; Sri Werastuti, Desak Nyoman (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to analyze the effect of financial literacy on business performance and its impact on MSMEs’ loan repayment performance in Buleleng Regency. This research employs a quantitative approach with MSMEs in Buleleng Regency as the population, totaling 66,368 business units. The sample was determined using the Slovin formula with a 10% margin of error, resulting in a minimum sample size of 100 MSMEs in Buleleng Regency. The sample was selected using a purposive sampling technique. Data were collected through questionnaires distributed directly to MSME owners. The data collection method utilized a questionnaire measured on a 1-4 Likert scale. Data analysis was conducted using Structural Equation Modeling Partial Least Squares (SEM-PLS) with the assistance of SmartPLS version 3 software. The results indicate that financial literacy has a positive effect on business performance and loan repayment performance, business performance has a positive effect on loan repayment performance, and financial literacy influences loan repayment performance through business performance.